1988
DOI: 10.1111/j.1570-7458.1988.tb01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea aphid performance and behaviour on two resistant cowpea lines

Abstract: In a series of laboratory and climate chamber tests we compared the growth and behaviour of Aphis craccivora on one susceptible (ICV-1) and two aphid-resistant (ICV-11 and ICV-12) cowpea lines. The aphids' growth rates were much lower on the resistant cowpea lines than on the susceptible one, indicating strong antibiosis. In addition, the aphids invariably settled in higher numbers on the susceptible line than on either of the resistant. Compared to ICV-1, damaged leaves of the resistant line ICV-12 were settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
5
12
1
1
Order By: Relevance
“…Therefore, results of this work and the other studies indicate that both antibiosis and antixenosis are mechanisms of A. craccivora resistance in ICV-12. This is consistent with findings in similar studies with ICV-12 and other resistant cowpea cultivars (Givovich et al 1988;Firempong 1988;Ofuya 1988a, b). Also, it is obvious from the laboratory study in this work and the aforementioned complementary studies that the factor that is responsible for ICV-12 resistance against the aphid is based in phloem sieve elements in seedling foliage.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, results of this work and the other studies indicate that both antibiosis and antixenosis are mechanisms of A. craccivora resistance in ICV-12. This is consistent with findings in similar studies with ICV-12 and other resistant cowpea cultivars (Givovich et al 1988;Firempong 1988;Ofuya 1988a, b). Also, it is obvious from the laboratory study in this work and the aforementioned complementary studies that the factor that is responsible for ICV-12 resistance against the aphid is based in phloem sieve elements in seedling foliage.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to the trend observed in tests on whole plants, expression of plant resistance on aphid life table parameters on excised seedling leaves ofICV-12 were stronger than that observed for ICY-12. This suggests that injury to plants through excision did not alter the adverse effects of ICY-12 on aphid performance, contrary to observations by Givovich et al (1988).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Nymphal survival, development and fecundity were all generally severely affected (Table 1), particularly for clones N4 and N2, indicating a high level of resistance to the cowpea aphid, probably because of antibiosis (Painter, 1951). Givovich et al (1988) observed much lower growth rates for A. craccivora on resistant cowpea lines than susceptible ones and they suggested strong antibiosis as the resistance mechanism. However, Saxena (1985) suggested that failure to survive may be caused not only by antibiosis, but also by a failure to obtain an adequate food supply; this could belong to the feeding non-preference category of resistance.…”
Section: Discussionmentioning
confidence: 95%
“…์ด๋Ÿฌํ•œ ์ €ํ•ญ์„ฑ ํ’ˆ์ข…์„ ์„ ๋ฐœํ•˜๊ธฐ ์œ„ํ•ด์„œ ํ’ˆ์ข…๋ณ„ ๋Œ€์ƒ ๊ณค์ถฉ์˜ ์ƒ๋ช…ํ‘œ๋ฅผ ์ž‘์„ฑํ•˜๊ฑฐ๋‚˜ EPG์™€ ๊ฐ™์€ ์ „๊ธฐ์ƒ๋ฆฌํ•™์  ๊ธฐ๋ฒ•์„ ํ†ตํ•ด ์„ญ์‹ํ–‰๋™์„ ์ธก์ •ํ•˜์—ฌ ๋น„๊ตํ•œ ์—ฐ๊ตฌ๊ฒฐ๊ณผ๋“ค์„ ํ™•์ธํ•  ์ˆ˜ ์žˆ ๋Š”๋ฐ, ๊ตญ๋‚ด์—์„œ๋Š” ๋ณต์ˆญ์•„ํ˜น์ง„๋”ง๋ฌผ์˜ ๊ธฐ์ฃผ์‹๋ฌผ์˜ ํ’ˆ์ข…๋ณ„ ์„ฑ์ถฉ์ˆ˜ ๋ช…๊ณผ ์‚ฐ์ž์ˆ˜๋ฅผ ์กฐ์‚ฌํ•˜๊ฑฐ๋‚˜ (Song and Motoyama, 1996;Choi et al, 2001;, ๋ฐœ์œก๊ธฐ๊ฐ„, ์ƒ์กด์œจ, ์‚ฐ๋ž€์œจ์„ ์กฐ์‚ฌํ•˜ ์—ฌ ์ž‘์„ฑํ•œ ์ƒ๋ช…ํ‘œ๋กœ ์œ ์ „์ž๋ณ€ํ˜•์ž‘๋ฌผ๊ณผ ๋ชจ๋ณธ ์ž‘๋ฌผ๊ฐ„์˜ ์ฐจ์ด๋ฅผ ํ™• ์ธํ•˜๊ธฐ๋„ ํ•˜์˜€๋‹ค (Kim and Kim, 2004). (Billy et al, 1997;Givovich et al, 1988;Ofuya, 1988). Billy et al(1997), Ruggle and Gutierrez (1995), Guldemond et al(1998) …”
unclassified